Experimental and theoretical studies on C-band bismuthbased erbium doped fiber amplifier - Parvizi, Roghaieh; Emami, Siamak Dawazdah; Shahi, Sharifeh; Harun, Sulaiman Wadi; Ahmad, Harith (INOE, 2009)
A performance of the Bismuth-based Erbium-doped fiber amplifier (Bi-EDFA) is experimentally and theoretically investigated using 1480nm forward pumping scheme. In the theoretical analysis, the rate and power propagation equations are solved to examine the effect of fiber length on the bandwidth of the gain spectra. At C-band region, the small signal gain of the Bi-EDFA varies from 20 to 23dB with 49cm long Bi-EDF and 150mW of 1480nm pump power. It is shown that the calculated gain and noise figure are in good agreement with the experimental results, verifying the feasibility of our theoretical model. However, the experimental result shows a relatively lower gain and higher noise figure compared to the theoretical result due to the spurious reflection in the cavity and insertion loss of the Bi-EDF which were neglected in our theoretical model.